UPAYA MENINGKATKAN MOTIVASI BELAJAR SAINS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS IV SD NEGERI 101768 TEMBUNG - Zuraidah Zuraidah (PGSD Universitas Negeri Medan, 2018)
This study aims to increase students' motivation to learn science through STAD type cooperative learning. This research is a classroom action research consisting of two cycles. Data collection tool is done by observation and giving questionnaires in each cycle. Based on the results of the questionnaire and observations showing the existence of learning motivation by applying STAD type cooperative learning in increasing the motivation to learn science, it was seen from the average student questionnaire obtained in the initial conditions of 32 students, only 1 student (3.12%) who had high learning motivation, 8 students (25%) whose learning motivation was moderate and 23 students (71.87%) whose learning motivation was low, then in the first cycle it was obtained with the student learning level of 32 students amounting to 10 students (31.12%) whose learning motivation was high , 12 students (37.5%) who had moderate learning motivation and 10 students (31.25%) whose learning motivation was low. On the second cycle, there were 29 students (90.62%) who had high learning motivation, 3 students (9.37%) whose learning motivation was moderate. Can be seen an increase in students from each cycle, so it can be concluded that the application of STAD type cooperative learning can increase motivation to learn elementary school science.Keywords: Motivation, Learning, Cooperative Learning type STAD